2011
DOI: 10.1260/1369-4332.14.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of the Shear Resistance of Corrugated Perfobond Rib Shear Connections

Abstract: Push-out tests were carried out to examine the shear strength of corrugated perfobond rib shear connections. The corrugated perfobond rib shear connection, formed by folding the straight perfobond rib steel panel, can be expected to increase the shear capacity and ductility of a shear connector due to the shear resistance and deformation of the inclined rib panel. To examine the shear behaviour of the corrugated perfobond rib connection and compare it with that of the perfobond rib, the push-out specimens were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In order to further improve the connection performance between steel and concrete, the PBL shear bond is proposed by scholars. It is found that increasing the opening area and the thickness of the steel plate can improve the bearing capacity and ductility of the members [16][17][18][19]; setting flanges can significantly improve the bearing capacity of shear keys and increase the constraint range of concrete slabs [20][21][22]; inserting steel bars at the opening can improve the bearing capacity of shear keys, and the deformation capacity is also significantly improved [23][24][25]. Under external pressure, the shear capacity increased slightly [26].…”
Section: Introductionmentioning
confidence: 99%
“…In order to further improve the connection performance between steel and concrete, the PBL shear bond is proposed by scholars. It is found that increasing the opening area and the thickness of the steel plate can improve the bearing capacity and ductility of the members [16][17][18][19]; setting flanges can significantly improve the bearing capacity of shear keys and increase the constraint range of concrete slabs [20][21][22]; inserting steel bars at the opening can improve the bearing capacity of shear keys, and the deformation capacity is also significantly improved [23][24][25]. Under external pressure, the shear capacity increased slightly [26].…”
Section: Introductionmentioning
confidence: 99%
“…In case of embedded trapezoidal webs, the most common shear connectors are horizontally placed headed studs and perfobond connections. Horizontally placed headed studs was investigated by Raichle [2] completed in a design proposal, perfobond and other type of shear connectors was investigated by Kim et al [3]. Besides these connectors, so-called concrete dowels (see on Figure 1) are also investigated actively [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these studies, simplified design methods for shear connection at ultimate limit state were proposed. Kim et.al [26] carried out push-out test of corrugated perfo-bond rib shear connections. Test results showed that the failure was determined by concrete at inclined panel with small deformations, and shear strength increased much in comparison to standard perfo-bond rib connector due to the shear resistance of the inclined rib panel.…”
Section: Introductionmentioning
confidence: 99%